FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN MODAL KOPERASI PADA KUD SEGAR TANI DI SUNGAI UDANG KECAMATAN PAMENANG KABUPATEN MERANGIN - Rosmiati Rosmiati (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Cooperative capital does not diminish and obscure the understanding of cooperatives themselves, but in reality that any association that is engaged in the business, the capital has a very important position, and therefore the board is required to be more professional in carrying out their duties and responsibilities in managing the cooperative, with a good board skills will further enhance the trust and participation of members in exercising their rights and obligations. This research was conducted in the Village Unit Cooperatives Farmers Fresh Merangin District, which aims to determine the factors that affect the growth of capital               at Farmers Fresh Village Unit Cooperatives.This research is a qualitative descriptive study, in which researchers want to describe the situation and condition of the factors that influence the growth of capital in cooperatives Fresh Farmers Cooperative. The research was conducted in KUD Tani Fresh by the number of subjects or informants are 4 people are: chairman, secretary, treasurer and one of the representatives of the employees.The findings suggest that the factors that affect the cooperative capital partumbuhan education level, and management level pendapatn cooperative, then the interview is happening in the field is the development of co-operative capital is also influenced by the credit crunch and electricity fee, and at some point in the event the price of fruit is too cheap or dropped so that could affect the development        of            co-operative         capital.It is suggested that the entire board of the cooperative can pay attention to the factors that affect the cooperative capital, so the development of co-operative capital to develop properly, then the board members or the cooperative and all parties associated with lending to the cooperative to be able to cooperate in the settlement perkreditannya so that no bad debts.Keywords: Factors affecting the growth of capital